Estimation of Heterosis, Heterobeltiosis and Potence Ratio Over Environments Among Pre and Post Green Revolution Spring wheat in Pakistan - Amarah Batool; Ijaz Rasool Noorka; Muhammad Afzal; Ali Hassan Syed (Journal of Basic & Applied Sciences, 2013)
Globally wheat trade has a major and impacting role in political and economic relationships between nations. Twelve pre-green revolution and post green revolution wheat genotypes viz., Sehr-06, Pasban-90, C-273, Pari-73, SA-42, Fsd-08, Chenab-70, Blue Silver, Lasani-08, Pak-81, Uqab-2000, and Pothowar-73 and their direct and reciprocal crosses were evaluated. The study concluded significant differences and highest values in heterosis, heterobeltiosis and potence ratio were found among genotypes and their cross combinations for pollen viability (Sehr-06 × Blue Silver), flag leaf area (SA-42 × Fsd-08), number of grains per spike (Pak-81× Lasani-08) and grain yield plant-1 (Chenab-70 × Fsd-08). Under changing climatic condition and limited water provision an amalgamation of pre-green revolution and post green revolution may provide a genetic diversity to break the stagnant yield barrier to ensure food security.